Organic Field Effect Transistors II 2003
DOI: 10.1117/12.508846
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting field-effect transistor: simple model and underlying functional mechanisms

Abstract: We report on light emission on organic thin film transistors of tetracene and polyfluorene (Poly(9,fluorene) (PF2/6)). The utilized transistor structure is a bottom gate configuration with interdigitated source and drain electrodes on a Si/SiO 2 substrate with a channel length of 5 µm. Light emission occurs above a source drain voltage of 30V even if the gate voltage is higher than the drain voltage. The light output can be controlled by the gate voltage. The light emission occurs close to the drain electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…4 Ever since, other research groups have published results on tetracene-based LEOFETs, dealing with experimental 5,6 as well as theoretical aspects. 7,8 This same basic type of LEOFETs, based on one unipolar organic semiconductor, has also been realized using polymers 9, 10 and doped small molecules 11 as the organic semiconductor. Electroluminescence in these LEOFETs occurs very close to the electron injecting metal electrode.…”
Section: Introductionmentioning
confidence: 99%
“…4 Ever since, other research groups have published results on tetracene-based LEOFETs, dealing with experimental 5,6 as well as theoretical aspects. 7,8 This same basic type of LEOFETs, based on one unipolar organic semiconductor, has also been realized using polymers 9, 10 and doped small molecules 11 as the organic semiconductor. Electroluminescence in these LEOFETs occurs very close to the electron injecting metal electrode.…”
Section: Introductionmentioning
confidence: 99%
“…It was not possible to operate the transistor in a pure electron accumulation mode. The S-shape at low-voltages in the output characteristics originates from an injection barrier for holes at the source electrode [8]. In the transfer characteristics (not displayed) an unusual saturation is observed, which can be attributed to contact resistors as detected by computer simulation [8].…”
Section: The Organic Light-emitting Field-effect Transistor (O-left)mentioning
confidence: 94%
“…In a more recent study light emission was also demonstrated in non-underetched OFET structures, but the transport was also found to be unipolar and the emission originated at the drain contact only. In a theoretical study by Schmechel et al [8] In the present study the still open question of electron injection at the gold tetracene contact is investigated by XPS and UPS. Based on the obtained values for the injection barriers a new technique of interface doping with calcium is introduced in order to increase the electron mobility in the investigated materials.…”
Section: Introductionmentioning
confidence: 98%
“…Interdigitated electrodes were first adapted to achieve a high device width (W) to length (L) ratios in a limited layout space in metal oxide semiconductor field-effect transistors (MOSFET). 1,2) Organic thin-film transistors (OTFTs) also employed these structures to increase ON-current characteristics, 3,4) while bi-polar power transistors have generally used comb-like contact electrodes to minimize current crowing. 5) Recently, the comb-shaped electrodes have been also used in field-effect hydrogenated amorphous silicon (a-Si:H) solar cells to enhance the output power.…”
Section: Introductionmentioning
confidence: 99%